Competition Ethics in Business According to Islamic Views - Fadhlur Rahman; Nadila Nadila; Rina Anggraini; Achmad Zulfikar Siregar (SEAN Institute, 2022)
Islamic Business Ethics is an important thing in the course of a professional business activity, and shows that there is a stand-alone structure that is separate from other structures because business ethics in Islam explains more about policies and truths both at the level of intentions and ideas towards behavior, starting from law Islam to trade relations. Trade in Islam has now begun to show its fangs. This is due to the collapse of the capitalist economy due to the global crisis. And in everyday life a person will never be separated from economic activities, especially Islamic economics. In practice, Islam recommends that it be based on Islamic law, namely the Al-Qur'an and As-Sunnah.